Effects of herbicides and mulch on the soil carbon, nitrogen, and microbial composition of two revegetated riparian zones over 3 years - Negar Omidvar; Steven M. Ogbourne; Zhihong Xu; Joanne Burton; Rebecca Ford; Babak Salehin; Iman Tahmasbian; Ruby Michael; Rachele Wilson; Shahla Hosseini Bai (Journal of Soils and Sediments, 2023)
Purpose Revegetation of riparian zones is important to improve their soil nitrogen (N) dynamics and to preserve their microbial compositions. However, the success of revegetation projects currently depends on weed control to reduce non-target vegetation competing over nutrients and to ensure the target plant species growth and survival. Different weed control methods affect soil microbial composition and N cycling. However, the long-term effects of herbicides on soil nitrogen (N) pools and microbial community composition remain uncertain even after cessation of the herbicide application. Materials and methods This study compared the impacts of different herbicides (Roundup ® , BioWeed™, Slasher ® , and acetic acid) with mulch on soil N dynamics and microbial community structure 3 years after vegetation establishment (herbicides applied repeatedly in the first 2 years after which no herbicides were applied in the third final year). Results and discussion Soil microbial biomass carbon (MBC) was significantly higher in mulch compared with Roundup ® , BioWeed™, Slasher ® , and acetic acid at month 26 at the Kandanga site and month 10 at the Pinbarren site. Soil MBC remained significantly higher in mulch compared with Roundup ® and BioWeed™, 12 months after the cessation of herbicide application at the Pinbarren site. Soil MBC in the Roundup ® and BioWeed™ groups was also lower than the acceptable threshold (160 mg kg −1 ) at month 34 at the Pinbarren site. Soil NO 3 − -N was significantly higher in the mulch than the Roundup ® at months 22 and 34 after revegetation at the Pinbarren site which could be partly explained by the decreased abundance of the denitrifying bacteria ( Candidatus solibacter and C. koribacter ). Additionally, both soil bacterial and fungal communities at the Pinbarren site and only fungal community at the Kandanga site were different in the mulch group compared with all other herbicides. The differences persisted 12 months after the cessation of herbicide application at the Pinbarren site. Conclusion Our study suggested that the application of mulch to assist with riparian revegetation would be beneficial for soil microbial functionality. The use of herbicides may have long-lasting effects on soil microbial biomass and diversity and therefore herbicides should be used with caution as part of an integrated land management plan.